Identifikasi Konfigurasi Geometri Bangunan Tahan Gempa - Livian Teddy; Johannes Adiyanto; Husnul Hidayat (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Indonesia is an earthquake-prone area because it is located at the world's most active tectonic plates and hundreds of local faults. Obviously, there have been many earthquake victims caused by collapsed buildings, hence the need for earthquake-resistant construction. However, there is not much guidance for architects to design earthquake-resistant buildings. This research proposes guidance for architects on how to design building forms relatively able to resist earthquakes. The simulation experiment method involving 32 building models in various forms was employed. The experimental results were then analyzed with modal analysis in ETABS and SVA for architectural design. Based on the analysis report, some guidelines were proposed: 1). Avoid buildings that are too slender, use the slenderness ratio H/D ≤ 2, 2). Avoid soft stories where the ratio of the top column height (h) to the bottom column height (h1) ≤ 0.8, 3). Use symmetrical shapes with 1 or 2 axes and avoid shapes with random compositions, 4). Use the additive and subtractive mass transformation ≤ 15%, 5).Strengthen the structural elements, install shear walls, or use dilatation to minimize potential torsional irregularities and non-parallel system irregularities of L, T, U, +, and Z forms6). Avoid using non-axial asymmetrical forms.